To the ones in need or the ones you need? The political economy of central discretionary grants - Empirical evidence from Indonesia - Gerrit J. Gonschorek; Günther G. Schulze; Bambang Suharnoko Firmansyah Sjahrir Putra (University of Freiburg, Department of International Economic Policy (iep), 2018)
We analyze the allocation of discretionary grants from the central government to local governments in Indonesia. Using OLS and Fixed Effects models on an unbalanced panel data set for more than 400 Indonesian districts covering the period 2005-2013, we investigate whether the allocation of the grants is determined by the need of a district, by political alignment of the central government with the local district heads, or by reelection motives of the incumbent president. We find that grant allocations are not determined by need characteristics and that political considerations matter significantly. Districts with low support for the president received significantly more than the core supporting districts, especially in the year of national elections. This effect is limited to the first term of the president. In the second term, after which reelection is impossible, political considerations were largely absent. This pattern is consistent with the view that the incumbent president considers discretionary grants as an instrument to increase reelection probabilities. Unlike the evidence for most countries, we find no effect for political party alignment with local district heads. Our results are robust to the inclusion of a number of other variables capturing competing motives.
Keywords: 330